Artificial intelligence in finance challenges, opportunities and regulatory developments - Gurrea-Martinez, Aurelio; Remolina, Nydia (Edward Elgar Publishing Incorporated, 2023)
"This book provides a comprehensive analysis of the primary challenges, opportunities and regulatory developments associated with the use of artificial intelligence (AI) in the financial sector. It will show that, while AI has the potential to promote a more inclusive and competitive financial system, the increasing use of AI may bring certain risks and regulatory challenges that need to be addressed by regulators and policymakers. After analysing the technological foundations of AI, the book focuses on the use and regulatory challenges of AI in the banking, capital markets and insurance industries. It also analyses, compares and assesses the different strategies and international approaches that have been adopted to address the challenges raised by the use of AI. The book concludes by providing a holistic and cross-sectoral analysis of the use of AI in the financial sector. The comprehensive, interdisciplinary, and industry-relevant approach adopted in Artificial Intelligence in Finance will provide students, practitioners and academics interested in financial markets with a broad understanding of the challenges and opportunities of AI in the financial sector. Additionally, the comparative and policy-oriented approach also adopted in the book will provide regulators and policymakers with innovative ideas and regulatory solutions that will help them address some of the most critical challenges associated with a new data-driven financial system"--